Peran Kegiatan Keagamaan Sekolah dalam Meningkatkan Kedisiplinan Ibadah Siswa Di SDN 1 Gunting Sukerjo Pasuruan - Siti Izatul Karima; Achmat Mubarok; Wiwin Fachrudin Yusuf (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to analyze the role of school religious activities in improving students’ worship discipline at SDN 1 Gunting Sukerjo Pasuruan. The research focuses on the implementation of religious activities such as congregational prayers, recitation of the Qur’an, reading Asmaul Husna, prayers before and after learning activities, and Islamic holiday commemorations as efforts to build students’ religious character and worship discipline. This study employed a descriptive qualitative approach with field research methods. The subjects of the research consisted of students in grades IV–VI, Islamic education teachers, the principal, and parents. Data were collected through in-depth interviews, participant observation, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing techniques, while the validity of the findings was ensured through triangulation and member checking. The results indicate that school religious activities play a significant role in improving students’ worship discipline through habituation, teacher role modeling, guidance, supervision, and reinforcement. Students showed improvements in punctuality, regularity, and obedience in carrying out worship activities both at school and at home. Supporting factors include teachers’ commitment, parental support, and a conducive religious school environment. Meanwhile, inhibiting factors include limited student motivation, environmental influences outside school, and inconsistent worship habits at home. Therefore, continuous and well-structured religious activities are essential in strengthening students’ spiritual awareness and developing disciplined worship behavior from an early age.